Responsabilidad social empresarial y su relación con los productos comercializados de los Almacenes Agrícolas, cantón Mocache, año 2015 - Galeas Macías, Edison Román (2016)
The research is based on an analysis of corporate social responsibility of agricultural stores in its marketed in the canton Mocache products. Currently the canton of Mocache has a population of 30,364 inhabitants. To extract the necessary information on research using surveys were made to the people, interview administrators agricultural stores canton Mocache, and then assess their corporate social responsibility mediantes the Ethos indicators, the same as will the information necessary to decision making. Fulfilling as manifested the first objective of the investigation it was determined that currently 57% of farmers in the canton Mocache is not satisfied by marketing products agricultural stores Mocache Canton this is due to organizational values are not covered , social and economic as part of its operations which does not allow them more committed to their customers, employees, communities and the environment. Through the interview administrator agricultural warehouse AGRIPAC S.A. Canton Mocache, the ing. Miguel Balseca said we can be considered as a voluntary practice for each of the agricultural warehouses development of corporate social responsibility because these applications can get more useful to the company, and the country does not have a law mandatory return your application. It is important to note that not all business leaders are willing to provide information in this regard. The company was AGRIPAC S.A., who showed greater willingness to assume corporate social responsibility to its customers, employees and community. Keyword • Corporate social responsibility, Agricultural warehouses, Products, Marketing, Ethos Indicators and Farmers.